STUDY ON THE DEVELOPMENT OF COORDINATING CAPACITIES IN GYMNASIUM EDUCATION STUDENTS - Petru Cornel BREAZ (Editura Universitatii Transilvania din Brasov, 2019)
The purpose of the current theme is to determine the level of knowledge and research, to identify the ideas underlying the study, but also the premises of the research ideas. The aim is to identify the optimal ways of recording and processing the obtained parameters and to highlight the interaction between the moments that contribute to the optimization of the coordinating capacities. The research hypothesis itself starts from the premise that performances in the field of coordinative capacities can be improved through operational models from the age of puberty. In applying the tests, an increase of the general physical development indices was observed; In conclusion, the specific means of different sports can replace the classical means